Bohr’s inequality for analytic functions with hyperbolic range - Yusuf Abu Muhanna; Issam Louhichi (Mathematics Open)
In this paper, we use properties of the hyperbolic metric and the modular function to show that Bohr’s radius for covering maps onto hyperbolic domains is [Formula: see text] This includes almost all known classes of analytic functions.